Pengaruh Motivasi Belajar dan Disiplin Belajar terhadap Hasil Belajar IPS pada Kelas VII MTsN 2 Bogor - Tholkhah, Imam; Enang Ipung, Enang Ipung; Amie Primarni, Amie Primarni (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine 1) There is a significant influence between learning motivation on social studies learning outcomes in class VII MTsN 2 Bogor. 2) The significant influence of learning discipline on social studies learning outcomes in class VII MTsN 2 Bogor. 3) The significant influence of learning motivation and learning discipline together on social studies learning outcomes in class VII MTsN 2 Bogor. This research is a quantitative research with a survey method. The population in this study were all class VII students of MTsN 2 Bogor for the 2022-2023 academic year, totaling 320 students. Data collection techniques using questionnaires and documentation. Test the validity of the instrument using product moment correlation and reliability test using alpha crombach's formula. Analysis prerequisite tests include normality tests, linearity tests and multicollinearity tests. The data analysis technique used is simple and multiple regression analysis. The results of this study indicate that 1) there is a significant influence between learning motivation on social studies learning outcomes after the coefficient of determination test is carried out, the R square value is 0.973 or 97.3%. This means that the learning motivation variable has a significant effect on social studies learning outcomes of 97.3%. 2) There is a significant influence between learning discipline on social studies learning outcomes. After testing the coefficient of determination, the R square value is 0.962 or 96.2%. This means that the learning discipline variable has a significant effect on social studies learning outcomes of 96.2%. 3) Based on the results of the determination test, the correlation value (R) between learning motivation and learning discipline on social studies learning outcomes is 0.989. This shows a correlation between learning motivation and learning discipline on social studies learning outcomes, with a coefficient of determination (R2) of 0.977 or 97.7%. Thus the variables of learning motivation and learning discipline have an influence on changes in social studies learning outcomes by 97.7%, while the remaining 2.3% is influenced by other variables not examined in this study.